2008
DOI: 10.1002/pds.1682
|View full text |Cite
|
Sign up to set email alerts
|

Drug information for patients—an update of long‐term results: type of enquiries and patient characteristics

Abstract: Purpose To analyse the type of enquiries to a drug information service in Germany, available exclusively for patients. Methods Sociodemographic characteristics of the patients who used the service, number and kind of drugs taken, existing diseases, reasons for enquiry as well as type of answers provided were recorded. For the present evaluation we analysed all enquiries to the service from August 2001 to January 2007. Results A total of 5587 enquiries were received. 5013 enquiries from 4091 patients were avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
4
5
0
2
Order By: Relevance
“…In this study, the majority of patients (67.9%) and callers (77.2%) were female, consistent with several other studies of queries to pharmacists [10, 11, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the majority of patients (67.9%) and callers (77.2%) were female, consistent with several other studies of queries to pharmacists [10, 11, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 91%
“…Callers regularly require quick advice about medications, such as actions to take when doses are omitted or taken accidentally, side effects, whether different medications will interact, or whether medications are safe for patients with certain conditions. Past research has focused on medication advice over the telephone targeting the public or healthcare professionals, provided by clinical pharmacologists, clinical pharmacists, poison specialists and clinical anaesthetists [1016]. Literature around nurses’ provision of telephone based medication advice is, however, lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the literature suggesting that women tend to seek health information more often than men [13,14,23], and for either themselves or a 'family' member [24]. It also aligns with data from other MCCs [25,26]. However, our study found a relatively high proportion of (young) males calling…”
Section: Characteristics Of (Antipsychotic) Medication Information Sesupporting
confidence: 92%
“…Safety as a goal of medicines information seeking is in agreement with literature about medicines information needs of consumers [8,44] and with findings from other MCCs [9,26,45].…”
Section: Narrative Of Medicine Information Seekingsupporting
confidence: 83%
“…Diese Angaben sollten hinsichtlich der Eigenschaften eingenommener NEM, des Informationsbedarfs hierzu und der Verbrauchercharakteristika ausgewertet werden.Am Institut für Klinische Pharmakologie der TU Dresden gibt es seit 2001 einen bundesweit agierenden Arzneimittelberatungsdienst für Patienten, der als Bestandteil der Unabhängigen Patientenberatung Deutschland (UPD) vom GKV-Spitzenverband geför-dert wird. Neben der Beantwortung von Anfragen zur Pharmakotherapie werden auch Informationen zu NEM bereitgestellt[12,10]. Alle Anfragen, die im Zeitraum von 2008 -2010 an den Arzneimittelberatungsdienst gestellt wurden, wurden dokumentiert und in einer relationalen Datenbank erfasst.…”
unclassified